Granulopoietic activity in Felty's syndrome. Issue 2 (April 1975) - Gupta, R; Robinson, W A; Albrecht, D
Abstract : The levels of urinary and serum granulopoietic factor have been determined in nine patients with Felty's syndrome and compared with similar levels in patients with rheumatoid arthritis without Felty's syndrome and patients with neutropenic disorders of other causes. These studies have shown that urinary and serum levels of colony stimulating activity (CSA) in patients with Felty's syndrome are low (mean urine CSA 10.0 and serum CSA 4.0) when compared to patients with neutropenic disorders without rheumatoid arthritis (mean urinary CSA 26.8 and serum CSA 9.4). These findings suggest that Felty's syndrome may be, in part, the result of decreased production or activity of granulopoietic factors rather than due simply to increased granulocyte destruction.